Supplementation of higher doses of Iron in programmes to control anaemia is a double edged sword - Mahajan, Preetam B; BS, Rama Krishna; Kapil, Umesh; Ramadass, Balamurugan (Indian Journal of Community Health, 2018)
Anemia is a major public health problem globally. Due to loss of 42.2 million disability-adjusted life years (DALYs) in 2011, Iron-deficiency anemia (IDA) was ranked among the top three major causes of disability in the world (1,2). IDA is responsible for at least 50% of anemia and is highly prevalent in India especially among women, children below 5 years, and adolescent girls (3) perhaps due to increased needs, insufficient dietary supplies, poor intervention coverage etc (4). Anemic girls will grow up to anemic mothers and in turn give birth to anemic children. Childhood anemia can have long term consequences. IDA has been associated with developmental deficits, impaired memory and neurodevelopment, diminished physical function, depression, fatigue, loss of vitality, preterm delivery, and lower infant birth weight (5–10). These, effects attributable to anemia remain invisible but are substantial (11), as it has serious health and economic costs and may hinder nation’s development. Therefore, effective and safe interventions are urgently needed across the lifecycle. The issue has attracted global attention and for the first time targets have been suggested like reducing the proportion of anemia among women of reproductive age (WRA) by 50% by 2025 in comparison to the baseline year 2011 (12). This is likely to add impetus to global efforts in reducing anemia and monitor the progress towards it.